Ethanol production using immobilized Saccharomyces cerevisiae in lyophilized cellulose gel - Winkelhausen, Eleonora; Velickova, Elena; Amartey, Samuel A; Kuzmanova, Slobodanka (Springer Nature, 2010)
A new lyophilization technique was used for immobilization of Saccharomyces cerevisiae cells in hydroxyethylcellulose (HEC) gels. The suitability of the lyophilized HEC gels to serve as immobilization matrices for the yeast cells was assessed by calculating the immobilization efficiency and the cell retention in three consecutive batches, each in duration of 72 h. Throughout the repeated batch fermentation, the immobilization efficiency was almost constant with an average value of 0.92 (12-216 h). The maximum value of cell retention was 0.24 g immobilized cells/g gel. Both parameters indicated that lyophilized gels are stable and capable of retaining the immobilized yeast cells. Showing the yeast cells propagation within the polymeric matrix, the scanning electron microscope images also confirmed that the lyophilization technique for immobilization of S. cerevisiae cells in the HEC gels was successful. The activity of the immobilized yeast cells was demonstrated by their capacity to convert glucose to ethanol. Ethanol yield of 0.40, 0.43 and 0.30 g ethanol/g glucose corresponding to 79%, 84% and 60% of the theoretical yield was attained in the first, second and third batches, respectively. The cell leakage was less than 10% of the average concentration of the immobilized cells.